Nanofabrication process by reactive ion etching of polystyrene nanosphere on silicon surface - Yabagi, Jibrin Alhaji; Kimpa, Mohammed Isah; Muhammad, Muhammad Nmaya; Nayan, Nafarizal; Embong, Zaidi; Agam, Mohd Arif (UTHM Publisher, 2017)
Nanospheres made of organic polymer have been applied to generate various patterning mask in fabricating functional nanostructures. The patterning and generation of semiconductor nanostructures through nanospheres mask provides a potential alternative to the conventional top-down fabrication techniques. Polystyrene nanosphere was modified using reactive ion etching (RIE) with O2 plasma at various duration of exposure (0, 20, 40 sec) and further extended to produce nanostructure by employing combination of O2 and mixed CHF3/SF6 gases. These edge PS nanospheres are later reduced as nanostructures and characterized using various characterization techniques such as Field Emission Scan Electron Microscopy/Energy Dispersive X-ray Spectroscopy (FESEM)/EDS, Atomic Force Microscopy and Fourier Transformation Infrared Spectroscopy (FTIR). The potential for multi stages etching procedures of O2 and later with SF6/CHF3 plasma etching are found to modify the nanospheres shapes and sizes which are important either as secondary mask for metal evaporation or as direct patterning of carbonaceous materials when exposed to irradiation sources. The nanostructures made using RIE will have applications in low power high performance electronic devices, optoelectronic, photovoltaic, biosensors and lithium ion battery devices.